Kombinasi Usahatani Kangkung, Bayam, dan Sawi di Kelurahan Landasan Ulin Utara Kecamatan Liang Anggang Kota Banjarbaru Provinsi Kalimantan Selatan - Anastasia Tri Astuti; Luthfi Fatah; Muhammad Husaini (Universitas Lambung Mangkurat, 2015)
Kecamatan Liang Anggang is one of the centers of horticulture production in Banjarbaru . However, farmers are still dealing with limited resource of capital, land, technology used, as well as resource allocation . In addition, small farmers have to deal with high ri sk and uncertainty. The study calculates the amount of costs, revenues, and gross margins of water spinach, spinach, and mustardgreen cultivation . The optimum combination of three vegetables, which gives the maximum revenue,subject to limited resources, is also discovered by using LINDO.By spending average cost IDR 2,936,409.86 per farming season, farmers in the area generate an average of revenue IDR 4,761,000.00, with an average gross margin IDR 1,824,590.14. After optimization, the farm income increase 94.86 percent. Based on the optimization using LINDO softw are, the maximum income is achieved by mustardgree n farming. It is the most valuable vegetables amon g others.